Study the effect of sound encodings on AD-HOC networks using TORA routing protocol and VOIP application: دراسة تأثير ترميزات الصوت على شبكات AD-HOCباستخدام بروتوكول التوجيه TORA وتطبيق VOIP - Suleiman Zidan Aldarf, Jamal Al-yassin (Journal of engineering sciences and information technology, 2019)
Mobile Ad-Hoc Networks are used for data transfer. The nodes of such networks do not require presetting. They are characterized by dynamic data transfer during their movement of the nodes. Routing protocols of mobile ad-hoc networks differ from the existing internet protocols which are designed for the fixed structure based wireless networks. MANET protocols have to face high challenges due to dynamically changing of topologies, low transmission power and asymmetric links. Due to link instability, node mobility and frequently changing topologies routing becomes one of the core issues in MANETs. Currently existent routing protocols provide routing solutions up to a certain level and most of them are designed and implemented in small areas. Many researchers are still working on the developments of MANET routing protocols. This research study effect of some voice codecs on ad-hoc networks using the (TORA routing protocol) and by running the VOIP application on a network randomized scenario. This effect will be compared through several performance parameters for the network used. The Network Simulation Program (OPNET), which is the first program in the area of telecommunications networks in general, is used to provide accurate results for studies in the field of networks.